Etika Komunikasi Dalam Al-Quran: Studi Tafsir Surat Al-Hujurat Ayat 1 – 8 - Fahimah, Siti (MADINAH, 2014)
In Islam there are regulations intended for his people, including about ethics. The success of a person is not determined by the intellect alone but also emotions, emotional intelligences is how someone could drown out his anger and focus more on moral or existing guidance. It was stated in the letter of al-Hujurat verses 1-8, which is a rule that humans have an obligation to put God as Kholik above all else, then the Prophet Muhammad as a lover, as good as any human morals to the apostles with a variety of conditions is essential, both named to the morals horizontally and are associated with private, to enhance a person kesholihan should be coupled with a vertically ie ethical morals to others critically, selective and thoughtful. Both are central to affect life and to achieve a pure success.